Safety of ethyl acrylate to be used as flavouring. (14th November 2017) - ,; Silano, Vittorio; Bolognesi, Claudia; Castle, Laurence; Chipman, Kevin; Cravedi, Jean‐Pierre; Engel, Karl‐Heinz; Fowler, Paul; Franz, Roland; Grob, Konrad; Gürtler, Rainer; Husøy, Trine; et al.
Abstract: The EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF Panel) was requested by the European Commission according to Art. 29 1(a) of the Regulation (EC) No 178/2002 to carry out a review of existing literature on the safety of ethyl acrylate [FL‐no: 09.037] when used as a flavouring substance. Ethyl acrylate [FL‐no: 09.037] was evaluated in 2010 by EFSA in FGE.71 as a flavouring substance, based on the 2006 JECFA evaluation. The Panel concluded that ethyl acrylate was of no safety concern at estimated level of intake as flavouring substance based on the Maximised Survey‐Derived Daily Intake (MSDI) approach. The Panel has evaluated the new literature available and any previous assessments performed by JECFA (2006) and EFSA (2010). Moreover, new data on the use levels of ethyl acrylate as flavouring substance have been provided. For use as flavouring substance, the chronic dietary exposure estimated using the added portions exposure technique (APET), is calculated to be 3, 545 μg/person per day for a 60‐kg adult and 2, 233 μg/person per day for a 15‐kg 3‐year‐old child. Exposure from food contact materials may be up to 6, 000 μg/person per day. The Panel considered that based on the available data, which covers all relevant genetic endpoints (i.e. gene mutations, structural and numerical chromosomal aberrations) there is no concern with respect to genotoxicity of ethyl acrylate. The Panel evaluated the available carcinogenicity studies conducted in rats and mice and agreed with the NTP evaluation (1998) concluding that the forestomach squamous cell papilloma and carcinoma observed in rodents were not relevant to humans. Additionally, there was no evidence of systemic toxicity in short‐term and subchronic toxicity studies. Therefore, the Panel concluded that there is no safety concern for the use of ethyl acrylate as a flavouring substance, under the intended conditions of use.